PERANCANGAN ILM BAHAYA KONSUMSI ROKOK AKIBAT INTERGENERATIONAL TOXIC MASCULINITY - Sari, Rani Nor Yunika; Setyanto, Daniar Wikan (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Adolescence is a transition phase towards adulthood which is marked by physical, behavioral, cognitive, biological and emotional changes. WHO defines adolescence as the period between the emergence of secondary sexual signs to sexual maturation and the transition to independence. The concept of toxic masculinity is a problem, reinforced by the culture of smoking which is seen as a symbol of masculinity. The increase in the number of teenage smokers in Indonesia is related to the transmission of smoking culture from generation to generation. Efforts to increase awareness about the dangers of smoking are carried out through social media such as Instagram. The use of visual animation video and strong messages on Instagram can be effective in increasing teenagers' awareness about the dangers of smoking and changing their perception of cigarettes as a symbol of masculinity. This research uses qualitative methodology. To collect data using interview, observation, literature and documentation methods. The aim of this research is to produce an effective Public Service Advertisement to raise awareness of the dangers of normalizing cigarette consumption due to Intergenerational Toxic Masculinity among adolescent boys in Semarang City which is disseminated via Instagram.